Cutaneous larva migrans - Aleksandra Wieczorek; Jacek Szepietowski (Termedia Publishing House, 2016)
Introduction . Cutaneous larva migrans (CLM) is a tropical zoonosis, caused by parasites, usually Ancylostoma braziliense. Humans are an accidental host. Polish patients with CLM are usually tourists visiting tropical and subtropical countries. The first symptoms do not always appear as creeping eruptions, which complicates the diagnosis. Objective. To present the case of a man with CLM after returning from Thailand to Poland and associated diagnostic difficulties. Case report. We present a case of a 28-year-old man who returned to Poland from Thailand. The first symptoms appeared as disseminated pruritic papules. No improvement after treatment with corticosteroids and antihistamines was observed. The diagnosis was established after the appearance of serpentine erythemas and improvement after albendazole therapy. Conclusions. In the case of returnees from exotic countries suffering from raised, pruritic rashes, and no improvement after treatment with corticosteroids and antihistamines, parasitic etiology should be considered.